Emerging epidemiological trends of multiple sclerosis among adults aged 20–54 years, 1990–2021, with projections to 2035: a systematic analysis for the global burden of disease study 2021 - Ling-yun Wang; Wen-fu Wang; Shu-yin Hui; Li Yang; Yue-xian Liu; Hang-juan Li (Frontiers in Neurology, 2025)
BackgroundOver recent decades, clinical, scientific, and public awareness of multiple sclerosis (MS) has increased significantly. This study aims to analyze global trends in the incidence, mortality, and disability-adjusted life years (DALYs) of MS among adults aged 20–54 years from 1990 to 2021.MethodsUsing data from the Global Burden of Disease (GBD) database, this study evaluated MS incidence, mortality, and DALYs in adults aged 20–54 years. Data from 204 countries and territories were stratified by age, sex, and geographical location. Annual percentage changes (APC) were calculated using Joinpoint regression, and estimated annual percentage changes (EAPC) were derived through log-linear regression modeling. Bayesian age-period-cohort (BAPC) modeling was employed to forecast future disease burden.FindingsGlobally, in 2021, there were 51,904.12 incident MS cases (95% UI, 44,998.80–59,073.37), 4,738.38 deaths (95% UI, 4,492.03–5,024.11), and 512,985.58 DALYs (95% UI, 428,133.20–610,308.62). Between 1990 and 2021, global incidence increased by 49.48% (95% UI, 44.34–55.15%), mortality rose by 18.21% (95% UI, 11.60–25.45%), and DALYs increased by 43.22% (95% UI, 36.79–48.94%). The High SDI region reported the highest rates of incidence (4.38 per 100,000; 95% UI, 3.93–4.83), mortality (0.41 per 100,000; 95% UI, 0.39–0.42), and DALYs (45.00 per 100,000; 95% UI, 37.22–53.12). Regionally, Western Europe had the highest number of cases (10,964.14; 95% UI, 9,572.30–12,318.88). At the national level, the United States reported the most MS incident cases in 2021 (9,388.21; 95% UI, 8,469.23–10,275.59). Sweden had the highest national incidence rate at 10.12 per 100,000 (95% UI, 8.69–11.66), with an EAPC of 0.24 (95% CI, 0.10–0.38).InterpretationThe global incidence, mortality, and DALYs associated with MS have shown increasing trends, although substantial variations persist across different SDI regions. A comprehensive understanding of MS epidemiology is essential for improving global disease prevention and control efforts.